Antibiotic Resistance in the Pediatric Intensive Care Unit: Literature Review - Nina Melina Ginting; Hendri Wijaya; Arlinda Sari Wahyuni; Yunnie Trisnawati; Rita Evalina; Ayodhia Pitaloka Pasaribu (Indonesian Journal of Global Health Research, 2025)
Antibiotics have been overused, the unwise use of antibiotics has become a special concern and has led to resistance. Almost 50% of antibiotic therapy is initiated inappropriately and without correct identification of the etiological agent. The high number of inappropriate antibiotic prescriptions contributes to the occurrence of antibiotic resistance and increased risk of death. MDR pathogens result in a 40% increase in mortality in hospital-acquired infections. The purpose of this study was to discuss the pattern of the resistance of antibiotic therapy in pediatric patients admitted to the PICU. Method: The search strategy was conducted through three databases (Google Scholar, Pubmed, Science Direct) which published during 2015-2025, using MeSH words “Antibiotic Resistance” AND “Pediatric intensive care unit”. There were thousand studies found, then by using the PRISMA flowchart, which total ten studies were included. PICU has a higher ratio of pathogen composition and bacterial resistance. Many factors can lead to antibiotic resistance, it might be caused by unnecessary or suboptimal prescribed antibiotic therapy from community before, previous health care and the hospital itself. The high number of inappropriate antibiotic prescriptions contributes to the occurrence of antibiotic resistance. Antibiotic resistance can lead to longer hospital stays and increased risk of mortality.